PENYULUHAN TENTANG SAMPAH BONGKOL NANAS YANG DIGUNAKAN SEBAGAI ANTISEPTIK DI DESA SIDODADI PATUMBAK - Nina Irmayanti Harahap; Angga Nugraha Sanjaya (INSTITUT KESEHATAN DELI HUSADA, 2021)
People use pineapples, one of which is as a cooking ingredient where pineapples are processed and eaten or can be served directly. However, what is not widely known by the public is that pineapple can be used as an antiseptic because pineapple has antibacterial activity. In the manufacture of this antiseptic where only the pineapple hump is used. So far, the pineapple weevil is known to the public only as garbage and cannot be used for anything, but the pineapple weevil can be used as an antiseptic, so that people can know and not throw away the pineapple weevil, but the community can use it as an antiseptic. With this counseling, the community in SidodadiPatumbak Village can know and practice what has been conveyed.